The Impact of Using the Strategies of the Listening Triangle and Carousel on the Achievement of Eighth Grade Male Students in Kurdish Grammar (Raparin Journal of Humanities (RJH), 2026)
The aim of this study is to examine the effect of using Listening Triangle and Carousel strategies on the academic achievement of eighth-grade male students in the subject of Kurdish grammar.The researchers used a quasi-experimental design with equivalent groups. The sample included eighth-grade male students from public boys’ schools in the Directorate of Eastern Education in the city centre of Duhok during totaling (2056) students in (16) schools for the academic year 2024–2025. The researchers intentionally selected Bzav School, and then randomly divided the students into two groups:Experimental group (D): 31 students Control group (A): 32 students.The experimental group was taught using the Listening Triangle and Carousel strategies, while the control group was taught the same subject using the traditional method.The researchers designed two types of lesson plans for each grammar topic: One using the Listening Triangle and Carousel strategies for the experimental group Another using the traditional approach for the control groupTo measure achievement, a test consisting of 35 items was developed, with psychometric properties considered for accuracy and reliability. After a season of teaching and the end of a semester, the researchers administered the test, collected data, and performed statistical analysis using the T-test.The results showed that the Listening Triangle and Carousel strategies had a positive and significant effect on the academic achievement of students in the experimental group.